Creación del departamento de recursos humanos para la Compañía inversionista Brisdal s.a. del cantón Buena Fé, provincia de Los Ríos - Muñoz Mero, José Lizandro (2013)
Investor Brisdal SA is a company that has farming in oil palm cultivation, rubber cultivation and short cycle crops and with the passing of the years is growing in your real estate and grows equally in personnel or human resources in meeting Los Rios province for the jurisdiction of Buena Fé Canton. Today at the business competition and in turn scale production volume is essential that every organization has the most precious resource you may have that organization as Human Resource, although this company despite having with a significant number of employees do not have a department that is responsible for the supervision and administration of personnel or human talent, so aforementioned has taken the decision to create the Human Resources Department in the Company Investor Brisdal SA, as executor of this research was required in the first instance socialize a dialogue with all staff of the company, subsequently continued to raise questions for staff and proceed with this tool surveys and interview staff and administrator respectively to hear that way the administration handled the staff. In the early socialization involving 68 collaborators indicate how important the company that runs the company creating the human resources department, as they indicate that the same attention is not a person in appropriate knowledge and has the experience in managing human talent that a person administering the entire company and empirically that perform the functions of the personnel department. What says the administrator involves prestige, importance, and solve problems through the company and even more when situations legal aspect of form and substance, also believes that the presence of a responsible professional and has experience staff in handling adverse situations prevent the proper development of the company and in turn the excellent working environment which is housed in the organization. Given the problems listed is given a proposed solution that involves creating human resources department so that this is responsible for the human talent and functions inherent to the position by a professional in the area, also gave know the importance of this project. As described above is carried out a technical and financial study as part of a specific objective to be this important to know the value of the investment in the creation of the human resources department for the company Investor Brisdal SA Likewise all the processes that are powers of the human resources department. And at the end of the project were presented the findings, recommendations and what the human resources department projected the future for the good of the company.